The Effect Of Applying Corn Leaf Flour And Seaweed To The Parts Of Broiler Chicken Carcasses Kept In Litter Cages - Sri Selvi Suudi; Ellen J. Saleh; Suparmin Fathan; Srisukmawati Zainudin (International Journal of Technology and Education Research, 2026)
The purpose of this study is to determine the effect of carcass parts on broiler chickens fed corn leaf flour and seaweed. This study used a Complete Random Design (RAL) with 6 treatments and 4 replicates. The treatment provided was the administration of seaweed flour and corn leaf flour to 96 broiler chickens aged 2 weeks. The experimental feed used in this study was P0 (commercial feed), P1 (10% corn leaf meal), P2 (10% seaweed meal), P3 (5% corn leaf meal + 15% seaweed meal), P4 (10% corn leaf meal + 10% seaweed meal), and P5 (15% corn leaf meal + 5% seaweed meal). The observed research variables were cut weight, chest weight, thighs, wings, and back. The results of this study were that corn leaf flour and seaweed flour did not have a real effect on the weight value of the chest, thighs, wings, and back. It was concluded that the application of corn leaf flour and seaweed had an effect on the weight of the broiler chicken carcass